Governance in the Digital Age: Factors of Influencing Citizen Engagement on the Government Websites (Lex localis - Journal of Local Self-Government, 2025)
With the development of smart cities, intelligent governance is naturally an indispensable component. Especially following the pandemic, many individuals have gained experience using e-government services. Nevertheless, significant progress is still required before e-government fully integrates into people's daily lives. How to encourage greater use of e-government has become a topic worthy of study. This paper, drawing from the UTAUT model, incorporates the variable of perceptions of the media use environment, which includes the factors of trust in the Internet, trust in the government and public value. This study findings indicate that the others variables, except performance expectancy and trust in the government, have an impact on use behavior. The conclusions can serve as a reference for governments worldwide in establishing and improving one-stop online government services.